INTERCULTURAL CITIZENSHIP IN THE EFL CLASSROOM: A SURVEY ON KAZAKHSTANI TEACHERS’ PERCEPTIONS: Received: 8th April 2024 Revised: 12th May 2024, 24th May 2024 & 29th May 2024 Accepted: 22nd April 2024 - Elmira Gerfanova; Zarina Rudik (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This study aimed to investigate how English as a foreign language (EFL) teachers perceive the concept of intercultural citizenship. The participants for this study were 23 EFL teachers from two universities in Kazakhstan. The primary method of data collection was a structured questionnaire containing open-ended items that asked the participants to express their thoughts and opinions on the qualities, responsibilities, and duties they believe are essential for an intercultural citizen. The obtained data revealed teachers’ perceptions of IC: teachers highlighted the importance of cultural awareness, empathy and intercultural communication skills. Moreover, the findings indicate that EFL teachers have a limited understanding of the concept of intercultural citizenship. The results of this study may provide insights for educators and curriculum developers into EFL teachers’ perceptions of intercultural citizenship, which may help to develop effective strategies and approaches for integrating the IC component into EFL classrooms.